Enabling real-time and high accuracy tracking with COTS RFID devices. (1st October 2020) - Zhao, Kai; Li, Binghao
ABSTRACT: RFID technology has been widely used for object tracking in the industry. Very high accuracy (centimetre level) positioning based on RFID carrier phase measurement has been reported. However, most of the proposed fine-grained tracking methods can only work with very strict preconditions. For example, some methods require either the reader or the tag to move along a certain one dimensional track at constant speed, while other methods need pre-deployed tags at known locations as reference points. This paper proposes a new approach which can track RFID tags without knowing the speed, the track and the initial location of the tag, and requiring only the antenna coordinates. The experiment results show that the algorithm can converge within 10 seconds and the average positioning accuracy can be at the centimetre level or even sub-centimetre level under different preconditions. The algorithm has also been optimised with a prediction-updating procedure to meet the requirements of post-processing and real-time tracking.